Association of Electronegative LDL with Macrophage Foam Cell Formation and CD11c Expression in Rheumatoid Arthritis Patients - Chang, Ching-Kun (Int J Mol Sci, 2020)
L5, the most negatively charged subfraction of low-density lipoprotein (LDL), is implicated in atherogenesis, but the pathogenic association is relatively unexplored in patients with rheumatoid arthritis (RA). We examined the role of L5 LDL in macrophage foam cell formation and the association of L5 with CD11c expression in THP-1 cells and RA patients. Using quantitative real-time PCR, we determined mRNA expression levels of ITGAX, the gene for CD11c, a marker associated with vascular plaque formation and M1 macrophages in atherogenesis, in 93 RA patients. We also examined CD11c expression on THP-1 cells treated with L5 by flow cytometry analysis and the plasma levels of inflammatory mediators using a magnetic bead array. We found a dose-dependent upregulation of foam cell formation of macrophages after L5 treatment (mean ± SEM, 12.05 ± 2.35% in L5 (10 µg/mL); 50.13 ± 3.9% in L5 (25 µg/mL); 90.69 ± 1.82% in L5 (50 µg/mL), p < 0.01). Significantly higher levels of CD11c expression were observed in 30 patients with a high percentage of L5 in LDL (L5%) (0.0752 ± 0.0139-fold) compared to 63 patients with normal L5% (0.0446 ± 0.0054-fold, p < 0.05). CD11c expression levels were increased in the L5-treated group (30.00 ± 3.13% in L5 (10 µg/mL); 41.46 ± 2.77% in L5 (50 µg/mL), p < 0.05) and were positively correlated with plasma levels of interleukin (IL)-6 and IL-8. L5 augmented the expression of IL-6, IL-8, and tumor necrosis factor-α (TNF-α) on monocytes and macrophages. Our findings suggest that L5 may promote atherogenesis by augmenting macrophage foam cell formation, upregulating CD11c expression, and enhancing the expression levels of atherosclerosis-related mediators.